Implementing principles of coronary heart disease secondary prevention into real-world clinical practice - D. M. Aronov; O. Yu. Sokolova; L. A. Gutkovskaya (Кардиоваскулярная терапия и профилактика)
The article is focused on practitioners' attitude towards clinical implementation of coronary heart disease secondary prevention programs. Using large-scale clinical trials' results, it is demonstrated that in most countries, secondary prevention measures are gradually improving. Russian secondary prevention programs are characterized by a substantial divide between clinical practice and international standards. In particular, Russian physicians use low doses of strategically important agents, and rarely recommend lipid-lowering therapy to their patients (17%).